Chromosomes of Aphidius ervi Haliday, 1834 (Hymenoptera: Braconidae). - Gokhman, Vladimir E.; Westendorff, Magdalene (Contributions to Entomology = Beiträge zur Entomologie, 2003)
Chromosome numbers of n=5 and 2n=10 were found in a few laboratory strains of Aphidius ervi Haliday, 1834 from Germany. However, several females having 2n=12 were detected in one of the populations studied. These females are likely to represent a thelytokous strain originating from an initially arrhenotokous one. The karyotype with 2n=12 has a characteristic additional pair of fully heterochromatic acrocentric chromosomes. Keywords Chromosomes, Aphidius ervi, Hymenoptera, Braconidae.